LEGAL NIGILISM IN MODERN UKRAINE: DEFINITIONS, CAUSES AND METHODS OF OVERCOMING - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article explores the concepts and signs of legal nihilism, the reasons for its emergence and ways of its overcoming. Research methods: to achieve the goal of the study were used general and specific scientific (special) methods. Results: the article considers the historical basis of the emergence of legal nihilism, the specific reasons for its emergence. The forms of expression of legal nihilism in Ukraine are indicated. It is noted that legal nihilism depends on the level of general culture, upbringing and legal awareness of the individual. Discussion: search for methods of overcoming legal nihilism in Ukraine. The contradictory nature of modern legal reality in Ukraine is due to the presence of two contradictory factors: the constitutional consolidation of the foundations of the rule of law, human rights and freedoms and the low level of legal culture, the mass spread of legal nihilism in all walks of life and government. The relevance of the research topic is due to the fact that legal nihilism can be a serious obstacle to socio-economic and state-legal reforms. The existence of legal nihilism directly affects the state of law and order in society, so to achieve real success in reforming society in conditions of economic and political instability is possible only if the distortions of legal consciousness and increase the level of legal culture. The author concludes that: the Ukrainian state is currently moving towards the moral, aesthetic, cultural and legal ideals of developed countries. In Ukraine at the present stage of development of statehood, the issue of legal education occupies a central place in the formation of personality, as based on recent events in society, the state needs citizens with patriotic heritage and national identity. As for the legal education of the individual, it creates a base in society, the foundation of legal awareness of the population. It is the legal culture of society and the individual, necessary to strengthen the principles of legal legitimacy and social justice in society, to create a moral atmosphere in which people can live freely and take an active part in shaping the system of state formation. It is an indicator of high civic activity and responsibility of citizens. That is, a citizen of every state who has a legal culture is a person who has civic courage and civil dignity, ready to defend the fundamental values of an open, free society, where the priority is the rights, interests and freedoms of man and citizen. As for the educational function of law, it is aimed at developing and strengthening legal awareness, legal culture and legal education of all members of society skills of lawful behavior. Only by joint efforts of state bodies, public organizations, the use of various, interdependent means, comprehensive expansion of legal education of citizens, increasing the role of public opinion in the fight against crime can succeed in ensuring the effectiveness of the educational function of law and eliminate legal nihilism in society.